Construction and Validation of Academic Stress Scale for University Students - Saima Noreen, Saba Ghayas, Shaista Khalid, Shumaila Mazhar Awan, (PJE, 2023)
The present study aimed to construct and validate an instrument to measure the academic stress among university students of Pakistan. Item construction of this instrument was based on literature review, interviews from university students and expert’s opinion. After pilot study exploratory factor analysis was performed on a sample of 477 student (226 men and 251 women), recruited from different departments of University of Sargodha, Pakistan. 26 items were retained after exploratory factor analysis with three well defined factors (1. Personal, Parental and Teachers’ attitude, 2. Perception of workload and examinations, 3.